Investigating atherosclerotic plaque phantoms for ultrasound therapy - Sotiriou, Michalis; Yiannakou, Marinos; Damianou, Christakis A. (My University, 2022)
The aim of the proposed study was to conduct a feasibility study using a flat rectangular (2 × 10 mm2) transducer operating at 4.0 MHz for creating thermal lesions in an arterial atherosclerotic plaque phantom. The proposed method can be used in the future for treating atherosclerotic plaques in human arteries.
Keywords: Atherosclerosis; Cardiac disease; High intensity focused ultrasound; Therapeutic ultrasound; Treatment